Educação sexual entre o público e o privado: a vida de prostitutas do centro de Fortaleza - Aranha, Francisca Karla Botão (2014)
The goal is to comprehend how the knowledge related to sex education, acquired and used by sex workers in their professional activity, interferes with their private lives, trying to understand if this knowledge is used with their significant others, when sex involves love and affection in the sex worker’s life outside her workplace. The concept of prostitution, which is, the way that is administrated, is different in different cultures and countries. Prostitution can be found in various places: streets, poor neighborhoods, rich neighborhoods, brothels that accept college girls, stores that make their female employees have surgeries, like liposuction or breast implants. That’s why our view as a researcher isn’t on prostitution as a whole, but in a specific way. It’s about female prostitution, according to the lives of sex workers in brothels in downtown Fortaleza, particularly Gata Garota. Therefore, we must first begin there, which is what’s called “public” (professional life), so we can get into their private lives. My experience as a researcher starts in a scientific initiation project, in which the subject was the educational practices in brothels in downtown Fortaleza. That made possible to notice a reality, unknown until then, full of tabus, which brought with it a world of new knowledge, acquired throughout this journey. This research’s intent is to know which layers of sex education, learnt and practiced in the professional lives of sex workers, interfere in their private lives. The study was made with the methodological procedure of a qualitative research, of ethnographic nature. Semi-structured interviews (informal conversations) were used as research instruments, which resulted in oral sources, besides field diaries, as another way to collect data. This way, their memories are used as an essential speech element, with which there was an intention of reconstructing a phase or aspect of the sex workers’ lives in downtown Fortaleza. It was concluded that sex workers, in their workplace, take care of their bodies, especially in ways related to sex education with their clients, and most of the women interviewed reflect that attitude in their private lives, with love involved. It was noticed that these sex workers put on “masks”, in order to get through a workday. It was observed that it was hard for them to maintain long-term relationships with their significant others, and it was explicit in their faces that they craved affection.